In Silico, Molecular Docking and In Vitro Antimicrobial Activity of the Major Rapeseed Seed Storage Proteins - Rahman, Mahmudur; Browne, Jessica J.; Van Crugten, Jacoba; Hasan, Md. Fahim; Liu, Lei; Barkla, Bronwyn J. (Frontiers in Pharmacology, 2020)
Background: In addition to their use as an edible oil and condiment crop, mustard and rapeseed (Brassica napus, B. juncea, B. nigra, B. rapa and Sinapis alba) have been commonly used in traditional medicine for relieving pain, coughs and treating infections. The seeds contain high amounts of oil, while the remaining by-product meal after oil extraction, a has a low value despite its high protein-content (~85%). The seed storage proteins (SSP) 2S albumin-type napin and 12S globulin-type cruciferin are the two predominant proteins in the seeds and could be used as a source for value adding to the waste stream, but information on their biological activities is scarce. In this study, purified napin and cruciferin were tested using in silico, molecular docking and in vitro approaches for their bioactivity as antimicrobial peptides. Methods: The 3D-structure of 2S albumin and 12S globulin storage proteins from B. napus were investigated to predict antimicrobial activity employing an antimicrobial peptide database survey. To get deeper insights into the potential antimicrobial activity of these SSP, in silico molecular docking was performed. The purified cruciferin and napin were then tested against Gram-positive and Gram-negative bacteria for in vitro antimicrobial activity by assessing the zone of inhibition of bacterial growth using the disk diffusion method. Results: In silico analysis demonstrated both SSP share similar 3D-structure with other well studied antimicrobial proteins. Molecular docking revealed that the proteins exhibited high binding energy to bacterial enzymes. Cruciferin and napin proteins appeared as a double triplet and a single doublet protein bands, respectively on SDS-PAGE and confirmed the presence of single proteins in each test samples. However, despite binding and sequence similarity to antimicrobial peptides, napin did not exhibit significant antimicrobial activity, even at the highest dose of 40 µg/20 µL, and cruciferin showed no antimicrobial activity beyond that of the solvent. Discussion: In silico and molecular docking results presented evidence for the potential antimicrobial activity of rapeseed cruciferin and napin SSP, however, in vitro activity did not support this. Further screening using different protein extraction and solubilization methods, and higher concentrations of the purified proteins may provide positive results.